113k views
5 votes
Tao wants to check that the expression 3(4x – 6) simplifies to 12x – 18. What is the value when 2 is substituted for x into both expressions? The value of each expression is 2. The value of each expression is 6. The value of one expression is 2, and the value of the other expression is 6. The value of one expression is 6, and the value of the other expression is –6.

1 Answer

5 votes

Answer:

The value of each expression is 6.

Explanation:

3 * 4 = 12 and 3 * 6 = 18

So 3(4x - 6) = 12x - 18

12(2) - 18 = 24 - 18 = 6

User Bradjive
by
5.8k points